Prospective study of health related quality of life before and after coronary artery bypass grafting: outcome at five years. Issue 4 (1st April 1999) - Caine, N; Sharples, L D; Wallwork, J
Abstract : OBJECTIVE: To determine the long term health related quality of life of coronary artery bypass graft patients, to look at changes between one and five years after surgery, and to examine the ability of preoperative variables to predict longer term outcome. DESIGN: Nottingham health profile (NHP) was used to assess patients at five years compared to results obtained at one year. PATIENTS: 100 male patients aged < 60 years at time of surgery; 77 had three vessel disease and 84 received three or more saphenous vein grafts. RESULTS: In comparing the five year results with those at one year, lower mean scores, indicating slight improvements, were seen in the NHP dimensions of pain, sleep, social isolation, and emotional reactions, whereas signs of deterioration were noted in the physical mobility and energy scores. Chest pain was experienced by 34 of 84 patients at five years compared with 17 of 89 patients at one year. The proportion of patients who were unrestricted in their activities ranged from 61–70% at five years compared with 82–88% at one year. Absence of dyspnoea before surgery, indicating relatively good left ventricular function, was a predictor of good outcome at both one and five years. CONCLUSIONS: Evidence of deterioration in physical function is compatible with expected decline in graft patency; specific rather than generic measures were most sensitive to this change.